Quantum Magneto-Optics in Graphene - Leonid Falkovsky (Photonics, 2015)
The optical conductivity of graphene in quantizing magnetic fields is studied. Both dynamical conductivities, longitudinal and Hall’s, are analytically evaluated. The conductivity peaks are explained in terms of electron transitions. The optical transitions obey the selection rule with Δn = 1 for the Landau number n. The light transmission and Faraday rotation in the quantizing magnetic fields are calculated.